SEASONAL ABUNDANCE OF SOIL ARTHROPODS IN FOREST AND AGRO ECOSYSTEMS IN WARANGAL DISTRICT, TELANGANA STATE, INDIA - Lakshmi Merugu, Esam Narayana (Chelonian Research Foundation, 2024)
ABSTRACTSoil arthropods play a crucial role in ecosystem functioning and their populations are influenced by seasonal and ecological factors. This study aimed to investigate the seasonal variations in the abundance of soil arthropods in forest and agro-ecosystems within Warangal district, Telangana, India. Soil samples were collected from two 10-acre sites—an agricultural field and a forest area—across three seasons: Summer, Monsoon, and Winter. Tullgren funnels were used to extract and identify arthropods, with their abundance recorded and analyzed for seasonal trends. Results indicated that Collembola was the most abundant order in the forest ecosystem throughout the year, with significant peaks during the Monsoon, while the agro-ecosystem showed higher abundance of Collembola and Orthoptera in the Monsoon. Protura and Thysanura were also more prevalent in the forest during Winter, and seasonal fluctuations were more pronounced in the agro-ecosystem. These findings highlight the differential impacts of seasonal changes on arthropod communities in various ecosystems, emphasizing the stability of forest environments compared to the more dynamic agro-ecosystems.